'Sometimes they're gammin, playing tricks, but sometimes it's ears.' The perspectives of urban parents and carers of young Aboriginal and Torres Strait Islander children on their journey to diagnosis of persistent ear health and hearing problems - Samantha F Harkus; Kylie AJ Caso; Sharron T Hall; Carmen Kung; Toni N Manton; Sarah J Murthy; Giselle AL Olive; Trumaine M Rankmore; Nikkita L Roberts; Meagan L Ward; Kelvin M Kong (Sax Institute, 2021)
Objectives: Data presented in this paper were gathered during the Urban Hearing Pathways study. The objective of the study was to investigate how access to, and availability of, ear health and hearing services contributes to the burden of avoidable hearing loss experienced by young, urban Aboriginal and Torres Strait Islander children and their families. The objective of this paper is to present the perspectives of parents and carers about awareness and concern in their community, detection and diagnosis of children's ear health and hearing problems in primary care, and impacts of delays in diagnosis on children and families. These perspectives are complemented by those of health professionals. Importance of study: The study findings address an evidence gap relating to factors that prompt an ear health and hearing check for young, urban Aboriginal and Torres Strait Islander children. They reveal the difficulties families experience in establishing a diagnosis of chronic ear disease and receiving the care they perceive will effectively addresses their child's needs. Study type: Qualitative study with surveys. Methods: The project team consisted of six Aboriginal researchers and 10 non-Indigenous researchers. Data collection tools and methods were designed by the project team. A total of 33 parents and carers completed surveys, and most also took part in interviews (n = 16) or focus groups (n = 16); 23 described their child's ear health journey. Fifty-eight service providers from the health, early childhood and community service sectors completed anonymous surveys and 26 were interviewed. Descriptive statistics were generated from survey data and thematic analysis was conducted for interview and focus group data. Results: Five main themes emerged from the analysis of parent and carer interviews: community knowledge and parent/carer recognition of signs of ear health and hearing problems; parent and carer action-taking; getting ear health and hearing checks; recognition of persistent problems; and impacts of delays on children and families. Conclusions: Reiterating previous findings, there is no evidence of a systematic approach to ear checks for this at-risk population. A significant proportion of parents and carers are noticing problems by watching their child's listening behaviours: early and reliable indicators of hearing status that can be harnessed. Some persistent ear health problems are being managed in primary care as acute episodes, thus delaying specialist referral and increasing developmental impacts on the child. Parents' and carers' practical recommendations for improving hearing health services are presented.